Prevalence and Determinants of Anaemia among Women aged 15-49 in Nepal: A Trend Analysis from Nepal Demographic and Health Surveys from 2006 to 2016 - Acharya, Devaraj; Adhikari, Ramesh; Simkhada, Padam (Asian Journal of Population Sciences, 2022)
Anaemia remains one of the major health problems throughout the world and is most common in underdeveloped or developing countries like Nepal. Most of the studies have presented and analysed the situation on a particular time basis that could be by chance. The paper intended to assess the trends of anaemia prevalence amongst reproductive-age women throughout the decade using nationally representative data. The study used the data from recent three Nepal Demographic and Health Surveys (NDHS) 2006, 2011, and 2016. More than one third (36%, 35%, and 41% in NDHS 2006/2011/2016 respectively) of women of reproductive age were anaemic. Data showed inconsistent trends of anaemia prevalence among the surveys years. The situation of anaemia has not been improved. It was even worse in the latest NDHS 2016. Policymakers should reconsider, re-evaluate, and revise the intervention programmes applied to reduce anaemia.